THE REPRESENTATION OF WOMAN IN SUPERHERO MOVIE ENTITLED “BIRDS OF PREY” BY CATHY YAN - Azi, Rahmawati; Nurmalasari, Fitriananingsih; Aso, La (Himpunan Sarjana Kesusastraan Indonesia, Komisariat Sulawesi Tenggara, 2021)
This study aims to analyze the representation of woman in